Increased yield pressure in the anal canal during sacral nerve stimulation: a pilot study with the functional lumen imaging probe. Issue 2 (21st August 2016) - Haas, S.; Liao, D.; Gregersen, H.; Lundby, L.; Laurberg, S.; Krogh, K.
Abstract: Background: Sacral nerve stimulation (SNS) is a well‐established treatment for fecal incontinence but its mode of action remains obscure. Anal sphincter function is usually evaluated with manometry but resistance to distension may be a more appropriate parameter than luminal pressure. The functional lumen imaging probe allows detailed description of distension properties of the anal canal. Our objective in this study was to characterize the impact of SNS on distension properties of the anal canal in patients with idiopathic fecal incontinence. Methods: We studied 10 women (median age 64 [44–79] years) with idiopathic fecal incontinence at baseline and during SNS. The luminal geometry of the anal canal was examined with the FLIP at rest and during squeeze and the distensibility of the anal canal was investigated during filling of the bag. Key results: All patients were successfully treated with SNS and the mean Wexner Incontinence Score was reduced from 14.9 ± 4 to 7.1 ± 4.8 ( P <.001). The pressure required to open the narrowest point of the anal canal during distension (yield pressure) increased from 14.5 ± 12.2 mmHg at baseline to 20.5 ± 13.3 mmHg during SNS ( P <.01). The pressure‐strain elastic modulus increased non‐significantly from 2.2 ± 0.5 to 2.9 ± 1.6 kPa, indicating increased stiffness of the anal canal. Conclusion and inferences: The yield pressure and the resistance to distension increased in response to SNS for idiopathic fecal incontinence. This will inevitably increase the resistance to flow through the anal canal, which may contribute to the benefits of sacral nerve stimulation. Abstract : Spatio‐temporal diameter map of the anal canal from a single subject. The changing colors from blue to red illustrate increasing diameter.